Pengaruh Variasi Konsentrasi Ekstrak Kulit Jeruk Nipis (Citrus aurantifola) terhadap Penurunan Angka Kuman Udara Indoor di RS “X” - Diana Aristiyanti; Tuntas Bagyono; Tri Mulyaningsih (Poltekkes Kemenkes Yogyakarta, 2020)
Hospitals are health care institution that provides complete personal health service for in-patient, outpatient, and emergency service. Therefore, disifenction activites are necessary in hospitals. One of natural ingredients that can be used as disinfectant is lime peel because contains fla-vonoids which are anti-bacterial substance. This disinfectant is applied using fogger as the me-dium for decreasing the number of aerial bacteria. The objective of the study was to identify the most effective concentration of lime peel extract against the decrease of aerial bacteria number. The method used was an experiment with pretest-posttest with control group design, and was conducted in May to June 2018 in Hospital X. The data were analysed using paired t-test. The highest mean difference of aerial microbe reduction was found in the UV treatment, i.e. 212,7 CFU/m3 (47.52%), meanwhile the lowest one was found in the 1% concentration treatment, i.e. 68,4 CFU/m3 (23%). At the 1,5% concentration, the descrease was 69,4 CFU/m3 (31%) and at 2% concentration it was 173 CFU/m3 (46%). The statistical analysis obtained p-value >0,05, which means that the reduction difference between treatments were not significant.